RETRACTED: DETECTION OF GENETICALLY MODIFIED RICE LOCALLY AVAILABLE IN PUNJAB, PAKISTAN - LATIF, A; SHAFIQUE, MT; BANO, M; BIBI, A; BIBI, T; GULNAZ, S; KHAN, RAR; MALLHI, AR; SARFRAZ, S; AHSAN, A; IQBAL, HMN; LATIF, A; et al. (Biological and Clinical Sciences Research Journal, 2023)
Retraction Notice: This paper has been retracted from the journal after receipt of written complains from IRB & Ethical Committee, National Institute for Biotechnology and Genetic Engineering, Pakistan. This journal is determined to promote integrity in research publication. This retraction is in spirit of the same. After formal procedures editor(s) and publisher have retracted this paper on 5th July-2023. Related policy is available here: http://bcsrj.com/ojs/index.php/bcsrj/AWP